Protective Effects of Protegrin in Dextran Sodium Sulfate-Induced Murine Colitis - Huynh, Evanna; Penney, Jenna; Caswell, Jeff; Li, Julang (Frontiers in Pharmacology, 2019)
Cathelicidins, a class of antimicrobial peptides, have been widely studied for their antimicrobial role in innate immune responses during infection and inflammation. At sub-antimicrobial concentrations, various cathelicidins from different species have been reported to exert chemotactic activity on neutrophils, monocytes, dendritic cells and T-cells, and also enhance angiogenesis and wound healing. To date, the role of the pig cathelicidin, protegrin-1 (PG-1), in immune modulation and tissue repair in the intestinal tract has not been investigated. The aim of the present study was to examine the potential protective effects of recombinant PG-1 in a mouse dextran sulfate sodium (DSS)-induced colitis inflammation model. This is the first report showing the protective effects of PG-1 in its various forms (pro-, cathelin-, and mature- form) in attenuating significant body weight loss associated with DSS-induced colitis (p<0.05). PG-1 treatment improved histological scores (P<0.05) and influenced the gene expression of inflammatory mediators and tissue repair factors such as trefoil factor (TFF3) and mucin (MUC-2). Protegrin treatment also altered the metabolite profile, returning the metabolite levels back closer to untreated control levels. These findings lay the foundation for future oral application of recombinant PG-1 to potentially treat intestinal damage and inflammation.